2012
DOI: 10.1111/j.1754-9485.2012.02393.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of stereotactic body radiation therapy for medically inoperable multiple primary lung cancer

Abstract: Introduction: To review outcomes of medically inoperable patients treated with stereotactic body radiation therapy (SBRT) for multiple primary lung cancer (MPLC). Methods: We retrospectively reviewed the charts of 10 patients (21 lesions) treated with SBRT for synchronous (seven), metachronous (one) or synchronous/metachronous lung cancers. All patients were male, medically inoperable and had a median age of 66 years. Eight patients had bilateral disease and two had unilateral disease. All patients had a histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Only a few SBRT studies have been published, with a relatively small number of patients. [15][16][17][18][19] According to previous reports on SBRT containing a relatively large number of SPLC patients, the 2-year OS was 56% to 61%, 18,19 which is comparable to this study. However, direct comparison between studies is difficult and of little meaning because of the small sample size and variation of the patient selection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Only a few SBRT studies have been published, with a relatively small number of patients. [15][16][17][18][19] According to previous reports on SBRT containing a relatively large number of SPLC patients, the 2-year OS was 56% to 61%, 18,19 which is comparable to this study. However, direct comparison between studies is difficult and of little meaning because of the small sample size and variation of the patient selection.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, there are few publications discussing the use of SBRT for SPLC. [15][16][17][18][19] This study evaluates the OS, progression pattern, and toxicity of SBRT as a definitive treatment for SPLC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews have demonstrated similar results but with much smaller numbers (10 patients). One report from the University of Oklahoma treated 10 patients with 21 synchronous/metachronous inoperable lung tumours with an 18 month local control rate of 95% [11]. The University of Indiana also published a series on 10 patients with an 18 month local control rate of 80% for patients with bilateral multiple biopsy proven non small cell lung cancers [7].…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility, safety, and efficacy of SABR for this purpose have been established by retrospective and prospective studies published over the past decade, and this technique has become a new standard of care for patients with medically inoperable stage I nonsmall cell lung cancer (NSCLC). However, the application of SABR for multiple early stage primary lung tumors has been described only rarely . The objective of this study was to explore the role of SABR for patients with MPLC.…”
Section: Introductionmentioning
confidence: 99%